Дополните предложения: This box might come < in useful one day.

Est19xx1 Est19xx1    3   17.04.2019 03:00    3

Ответы
KaDet1778 KaDet1778  03.06.2020 02:03

\frac{2x}{x-1} + \frac{3}{x+1} = \frac{3x11}{x^{2}-1}

2x(x+1)+3(x-1)=3x+1

2x^2+2x+3x-3-3x-1=0

2x^2+2x-4=0

x^2+x-2=0

x1=-2, x2=1

ПОКАЗАТЬ ОТВЕТЫ
leila12341 leila12341  03.06.2020 02:03

  2х  +  3   =  3х+1

х-1      х+1   х ^2 -1

2x(x+1)+3(x-1)=3x+1

2x^2+2x+3x-3-3x-1=0

2x^2+2x-4=0  :2

x^2+x-2=0

D=1-4*1*(-2)=9=3^2

x1=-1+3/2=1       x2=-1-3/2=-2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Другие предметы